Making Sex Revisited Dekonstruktion des Geschlechts aus biologisch-medizinischer Perspektive - Voß, Heinz-Jürgen (KörperKulturen, 2015)
Sex is made socially. That this also applies to the biological gender sex - a postulate of queer-feminist theories -, this volume can be determined by biological theories for the first time decidedly and differentiated. The natural-philosophical and biological-medical gender theories of different periods of time (antiquity, incipient modernity, present) are presented and associated with social gender orders. Heinz-Jürgen Voß differentiates the struggling positions and shows that with process-oriented approaches, many genders are conceivable in biological theories - instead of just two or three.